2016
DOI: 10.3390/nano6090173
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of g-C3N4 Nanosheets/ZnO Nanocomposites with Enhanced Photocatalytic Activity in Reduction of Aqueous Chromium(VI) under Visible Light

Abstract: Graphitic-C3N4 nanosheets (CN)/ZnO photocatalysts (CN/ZnO) with different CN loadings were successfully prepared via a simple precipitation-calcination in the presence of exfoliated C3N4 nanosheets. Their morphology and structure were thoroughly characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), UV-Vis diffuse reflectance spectroscopy (DRS) and photoluminescence spectra (PL). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(39 citation statements)
references
References 61 publications
(95 reference statements)
5
34
0
Order By: Relevance
“…As shown in Figure 3c, the ZnO nanoparticles exhibited a flocculent-like structure consisting of aggregated spherical ZnO nanoparticles with an average particle size of approximately 10 nm, which was in line with the SEM observations. The lattice fringes were measured to be 0.263 nm (Figure 3d), which was in agreement with the (002) facet of the hexagonal wurtzite ZnO phase [34]. From Figure 3e, it was observed that the Bi-ZnO-80 composite was composed of two kinds of constituent particles, one with a large diameter Bi and the other with a small ZnO.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…As shown in Figure 3c, the ZnO nanoparticles exhibited a flocculent-like structure consisting of aggregated spherical ZnO nanoparticles with an average particle size of approximately 10 nm, which was in line with the SEM observations. The lattice fringes were measured to be 0.263 nm (Figure 3d), which was in agreement with the (002) facet of the hexagonal wurtzite ZnO phase [34]. From Figure 3e, it was observed that the Bi-ZnO-80 composite was composed of two kinds of constituent particles, one with a large diameter Bi and the other with a small ZnO.…”
Section: Introductionsupporting
confidence: 73%
“…For bare ZnO, the peaks at 31.8° (100), 34.5° (002), 36.42° (010), 47.6° (102), 56.58° (110), 63.05° (103), and 67.9° (112) were highly identical with those of the ZnO hexagonal wurtzite phase (JCPDS-NO. [34]. For the BiNPs/ZnO with different Bi contents, the characteristic diffraction peaks of ZnO were weakened with an increased content of Bi metal.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The full spectrum of the ternary photocatalyst indicated the peaks corresponding to C 1s, O 1s, N 1s, Bi 4f, and Cl 2p, and no other characteristic peaks for other elements were detected, which approves purity of the photocatalyst (Figure A). The peaks, centered in the range of 280‐294 eV, are further deconvoluted into three different peaks centered at 284.8, 289.4, and 286.0 eV, corresponding to sp 2 (C=C), C–NH 2 group of the broad asymmetric C 1s feature of g‐C 3 N 4 nanosheets, and C–OH of CDs particles, respectively (Figure B) . The spectrum of O 1s shows three distinct prominent peal peaks at 530.3, 532.1, and 534.1 eV, which correspond to the oxygen of Bi–O, C–O–C, and C=O bonds, respectively (Figure C) .…”
Section: Resultsmentioning
confidence: 99%
“…Since this first report, many investigations and characterizations have been published with differing XPS results. [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Selected data are summarized in Ta ble S4 (Supporting Information), giving the binding energies for the C1sa nd N1ss ignals. Intriguingly, in most spectra,t he signal of C1sa ta round2 88 eV dominates the C1sr egion, but there are also spectra in which this peak exhibits the lowest intensity.T he most intense N1ss ignal ranges from 398.0 to 400.06eV ( Table S4).…”
Section: X-ray Photoelectron Spectroscopy Analysismentioning
confidence: 99%